PENGARUH TRUST TERHADAP CUSTOMER ENGAGMENT PADA AKUN LOUISSE SCARLETT FAMILT DIMEDIASI SWIFT GUANXI - Yunita, Sherly; Sander, Ongky Alex (Universitas Multimedia Nusantara, 2024)
Abstract- The differences in building consumer involvement in traditional and online commerce make the broadcasters and consumers have limitations in product buying and selling activities. Live streaming is currently used in many fields, including to market products. As live streaming involves many parties, it is difficult for the streamer to build trust in live streaming trading. Additionally, there is a different approach to building customer trust in offline and online channels. This research discusses the swift guanxi variable as a mediator between trust and customer engagement on the Louisse Scarlett Family account, the affiliate that has received many awards in 2022-2023. This study involved 201 respondents who had interacted and made transactions on the Louisse Scarlett Family live streaming. The results of this study show a significant direct influence between trust in broadcasters and swift guanxi and other trust dimensions are not significant in customer engagement. Besides that, trust has a significant effect on swift guanxi and swift guanxi mediates the effect of trust in the product on customer engagement and does not mediate trust in the broadcaster, or trust in the community on customer engagement. Building trust in live streaming trading will form stronger customer engagement and also build a more harmonious and reciprocal relationship in trading Keywords: Trust in Community; Trust in Broadcaster; Trust in Product; Swift Guanxi; Customer Engagement